2017
DOI: 10.1080/13825585.2017.1413166
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between stereotype threat, subjective aging, and memory in older adults

Abstract: This study examined whether the effects of stereotype threat on memory and subjective age were moderated by positive age stereotypes and self-perceptions of aging among older adults. Perceived threat as a mechanism underlying these effects was also explored. Results showed that stereotype threat (high vs. low threat) did not affect the dependent variables. Moreover, self-perceptions of aging did not moderate the effect of stereotype threat on the dependent variables. However, for people with more positive age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…The evidence on the link between subjective age and aging stereotypes is equivocal, and a direct examination of stereotype threat did not find evidence for a link to subjective age (57). Stereotypes of aging may be more relevant to some people than to others.…”
Section: Stereotypes Of Agingmentioning
confidence: 96%
“…The evidence on the link between subjective age and aging stereotypes is equivocal, and a direct examination of stereotype threat did not find evidence for a link to subjective age (57). Stereotypes of aging may be more relevant to some people than to others.…”
Section: Stereotypes Of Agingmentioning
confidence: 96%
“…Threat appraisal or perceived stereotype threat is often not assessed in studies of stereotype effects on memory. However, when perceived threat is measured, it generally does not differ between the stereotype groups and comparison groups as expected (but see Swift et al, 2013), but it is age-sensitive, negatively related to memory performance, and positively related to anxiety (Chasteen et al, 2005;Kang and Chasteen, 2009;Popham and Hess, 2013;Marquet et al, 2019). Chasteen et al, 2005) reported that perceived stereotype threat fully mediated the effect of age on memory performance, and later found that perceived stereotype threat moderated their stereotype manipulation, wherein memory performance was poorer for those in the stereotype group who also reported higher perceived stereotype threat (Kang and Chasteen, 2009).…”
Section: Introductionmentioning
confidence: 51%
“…Common "threat" paradigms include explaining that the purpose of the study was to compare the performance of older adults to that of younger adults and emphasizing the age-sensitive nature of the test. Researchers may even explicitly state that older adults are not expected to do as well because they are old, may include a younger adult confederate in the testing session (Kang and Chasteen, 2009;Popham and Hess, 2013;Swift et al, 2013;Fernández-Ballesteros et al, 2015;Mazerolle et al, 2017), or may ask participants to read news articles or watch videos describing age-related deficits in memory (Hess et al, 2003;Hess and Hinson, 2006;Thomas and Dubois, 2011;Wong and Gallo, 2018;Marquet et al, 2019). Researchers have also manipulated task instructions to emphasize or de-emphasize the memory component of the testing (Rahhal et al, 2001;Hess et al, 2004;Chasteen et al, 2005;Desrichard and Köpetz, 2005;Sindi et al, 2013;Bouazzaoui et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults can develop two different types of attitudes toward aging: positive and negative attitudes. Positive attitudes toward aging positively influence their physical and mental health, 3 quality of life, 4,5 life satisfaction, 6 stress response, coping strategies, 7 cognitive functions (e.g., verbal fluency, memory), 8–10 and healthy living behaviors 11 . Older adults with more positive attitudes toward aging tend to be more independent and face fewer difficulties when engaging in daily life activities 12 .…”
Section: Introductionmentioning
confidence: 99%